1992
DOI: 10.1093/ajcp/97.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Atrophoderma of Pasini and Pierini: An Immunopathologic Case Study

Abstract: Atrophoderma of Pasini and Pierini (APP) is a rare and distinctive form of dermal atrophy of uncertain origin. In only one previous report have immunopathologic methods been used to study a case of atrophoderma of Pasini and Pierini, and on the basis of the results obtained it was concluded that immunologic mechanisms were relevant to the pathogenesis of the condition. A detailed investigation of a case of atrophoderma of Pasini and Pierini was conducted using immunofluorescence and immunoperoxidase techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 0 publications
0
12
0
1
Order By: Relevance
“…When compared with adjacent normal skin, the dermal thickness is reduced. The sweat glands and the pilosebaceous units are not affected6,10.…”
Section: Discussionmentioning
confidence: 96%
“…When compared with adjacent normal skin, the dermal thickness is reduced. The sweat glands and the pilosebaceous units are not affected6,10.…”
Section: Discussionmentioning
confidence: 96%
“…The immunophenotyping disclosed inflammatory infiltrates of T lymphocytes and macrophages |6|. Positive staining of epidermal den dritic cells with anti-IgM antibody was reported as a char acteristic finding [13]. In single cases, IgM and C3 deposits were found in the blood vessel walls and occasionally at the basement membrane [6], However, IgM and C3 are not an infrequent finding in various cutaneous conditions, espe cially in connective tissue diseases, and we do not regard them as a characteristic feature.…”
mentioning
confidence: 99%
“…Electron microscopic study demonstrated macrophages and lymphocytes around vessels and between collagen fibers in the mid-dermis, and monoclonal antibody studies of the cells in the perivascular infiltrate demonstrated cells reacting with T cell and macrophages (9). These results suggest that immunological factors may play a role in the pathogenesis of IAPP.…”
Section: Discussionmentioning
confidence: 68%